Physico-chemical characteristics and microbiological quality of broiler chicken pectoralis major muscle subjected to different storage temperature and duration - Ab Aziz, Muhamad Faris; Hayat, Muhammad Nizam; Kaka, Ubedullah; Kamarulzaman, Nitty Hirawaty; Sazili, Awis Qurni (MDPI, 2020)
Storage temperature and duration plays an important role in meat processing. Observations in poultry processing plants have shown a serious deviation in storage condition compared to the recommended procedures. Furthermore, there is still a paucity of evidence on the effects of storage temperature and duration on meat quality and microbial population. The aim of this study was to determine the effects of different temperature and duration during storage on physico-chemical properties and microbiological quality of broiler chicken Pectoralis major muscle. Eighty birds were slaughtered and processed, following which the packed boneless breast (PBB) (each bird was to provide two breast muscle samples; left breast and right breast) was divided into four groups, each consisted of 40 PBB. Each group was subsequently assigned to storage either at 4 °C, -10 °C, -18 °C or -40 °C, for 24 h before 20 PBB samples from each group were transported to the respective laboratory for meat quality and microbiological analysis. The remaining 20 PBB from each storage temperature were stored for 72 h before being transported for analysis. Results have shown significant increases in drip loss and cooking loss as the storage temperature decreases. Similarly, storage duration significantly affected cooking loss, of which, samples stored for 72 h exhibited higher cooking loss compared to those stored for 24 h. For color, significant differences were only observed in lightness (L*) and redness (a*) values. Longer duration of storage had significantly improved tenderness whereby, samples that have been stored for a shorter duration presented higher pH values. Populations of coliform and Salmonella decreased significantly with decreasing temperature and increasing storage duration.